ANALYZING AISAS MODEL APPLICATION IN INSTAGRAM MARKETING COMMUNICATION: A CASE STUDY OF A MICRO BUSINESS - Adenia Safarani; Idola Perdini Putri (RADJA PUBLIKA, 2026)
Social media has become an important marketing communication channel for micro businesses, particularly in the food and beverage (F&B) sector. However, many micro businesses face human resource constraints, making it necessary to optimize the use of digital platforms. This study aims to analyze the implementation of marketing communication strategies on Instagram by an F&B microbusiness in Bandung Regency, using the AISAS (Attention, Interest, Search, Action, Share) model. A qualitative approach with a single-case study design was employed. Data were collected through in-depth interviews with eight purposively selected informants, supported by observations and documentation. The findings show that the business effectively utilized Instagram despite limited human resources. One of the key strategies identified was collaboration with micro-influencers, which helped increase brand visibility and reach target audiences more efficiently. The business also helped consumers find information through accessible content and active engagement on social media. Furthermore, positive consumer responses and content sharing helped expand the brand’s exposure and encourage a continuous AISAS cycle. This study suggests that effective marketing communication in micro businesses depends on the ability to deliver relevant content, engage consumers, and strategically collaborate with external parties such as micro-influencers to maximize marketing outcomes under resource constraints.